Admiralty and Secretariat : log books, etc. : supplementary series I : masters' logs [Adm. 54] (Australian Joint Copying Project microform collection.)
Log books and journals for ships on voyages to Pacific region - Acheron, Alligator, Anson, Beagle, Blenheim, Belleisle, Buffalo, Calliope, Cleopatra, Cockatrice, Pandora, Portland, Virago, Hermes, Camilla, Camelion, Childers, Cormorant, Favorite, Janus, Jupiter, Lee, Melville, Nimrod, North Star, Opossum, Orpheus, Osprey, Racehorse, Rattlesnake, Reynard, Sulphur, Samarang, Starling, Swift, Thalia, Torch, Vindictive, Volage, Wellesley, Pagoda, La Chiffonne.